2021
DOI: 10.1180/mgm.2021.20
|View full text |Cite
|
Sign up to set email alerts
|

Mn-bearing purplish-red tourmaline from the Anjanabonoina pegmatite, Madagascar

Abstract: A gem-quality purplish-red tourmaline sample of alleged liddicoatitic composition from the Anjanabonoina pegmatite, Madagascar, has been fully characterised using a multi-analytical approach to define its crystal-chemical identity. Single-crystal X-ray diffraction, chemical and spectroscopic analysis resulted in the formula: X(Na0.41□0.35Ca0.24)Σ1.00Y(Al1.81Li1.00Fe3+0.04Mn3+0.02Mn2+0.12Ti0.004)Σ3.00ZAl6 [T(Si5.60B0.40)Σ6.00O18] (BO3)3 (OH)3W[(OH)0.50F0.13O0.37]Σ1.00 which corresponds to the tourmaline species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 74 publications
(109 reference statements)
3
13
0
Order By: Relevance
“…The µ-LIBS spectra were acquired by AvaSpec Fiber Optic Spectrometer (390-900 nm with 0.3 nm resolution) with a delay of 2 μs after the second pulse and were integrated for 1 ms. Quantitative data were obtained by generating a linear regression using the main Li emission line intensity (670.706 nm corresponding to resonance transition 1s 2 2s > 1s 2 2p) particularly sensitive to Li amounts. The linear fit was made according to Bosi et al (2021) and revealed amounts of Li 2 O = 0.12 wt% (Table 1) in line with that estimated by the Pesquera et al ( 2016) approach (0.18 Li 2 O wt%).…”
Section: Micro-laser Induced Breakdown Spectroscopysupporting
confidence: 76%
See 2 more Smart Citations
“…The µ-LIBS spectra were acquired by AvaSpec Fiber Optic Spectrometer (390-900 nm with 0.3 nm resolution) with a delay of 2 μs after the second pulse and were integrated for 1 ms. Quantitative data were obtained by generating a linear regression using the main Li emission line intensity (670.706 nm corresponding to resonance transition 1s 2 2s > 1s 2 2p) particularly sensitive to Li amounts. The linear fit was made according to Bosi et al (2021) and revealed amounts of Li 2 O = 0.12 wt% (Table 1) in line with that estimated by the Pesquera et al ( 2016) approach (0.18 Li 2 O wt%).…”
Section: Micro-laser Induced Breakdown Spectroscopysupporting
confidence: 76%
“…Gonzalez-Carreño et al , 1988; Bosi et al , 2015b), indicate small amounts of W (OH). On the basis of previous investigations of Bosi et al (2012, 2016, 2021) and Watenphul et al (2016), the main broad FTIR band at ~3500 cm –1 is probably caused by the occurrence of the atomic arrangements 3[ Y (Mn 2+ ,Al) Z Al Z Al]– O3 (OH) 3 , whereas the bands above 3600 cm –1 may be caused by the arrangements Y [(Li,Fe 2+ ,Mn 2+ )(Mn 2+ ,Al)Al]– O1 (OH)– X (□), where □ = vacancy.…”
Section: Experimental Methods and Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Many attempts to define the X-P-T stability of tourmaline are known to date, the majority of which converge to breakdown temperatures confined between 700 and 920 °C, depending on composition, at pressures up to cally characterized before and after thermal treatment at 750 °C. In order to complete the study of Bosi et al (2021) with structural data from a treated sample, in situ structure behavior, and information on elbaite breakdown products, we applied a dual approach using both in situ and ex situ experiments, respectively, High-Temperature powder X-Ray diffraction (HT-pXRD) and single-crystal X-Ray diffraction (SC-XRD).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the studies of Bosi et al (2012Bosi et al ( , 2016Bosi et al ( , 2021 and Watenphul et al (2016), the four main FTIR bands between 3465 and 3587 cm -1 are likely caused by the occurrence of the atomic arrangements 3[ Y (Li,Fe 2+ ,Mn 2+ ,Al) Z Al Z Al]− O3 (OH)3. The bands between 3600−3700 cm -1 may be caused by the arrangements Y [(Li,Fe 2+ ,Mn 2+ )(Mn 2+ ,Al)Al]− O1 (OH)− X ( ), whereas the weak band above 3700 cm -1 may be ascribed to Y [(Li,Fe 2+ ,Mn 2+ )(Mn 2+ ,Al)Al]− O1 (OH)− X (Na).…”
Section: (Oh) Band Assignmentmentioning
confidence: 99%